2014
DOI: 10.4103/0970-9185.130011
|View full text |Cite
|
Sign up to set email alerts
|

Bedside prediction of airway length by measuring upper incisor manubrio-sternal joint length

Abstract: Background:Malpositioning of endotracheal tube may lead to serious complications like endobronchial intubation or accidental extubation. Using anatomical measurements for prediction of airway length would be more practical in resource constrained settings.Materials and Methods:One hundred adult patients of American Society of Anesthesiologists (ASA) grade 1 or 2, without any evidence of difficult airway, were randomly allocated to two cohorts — a model cohort of 70 (50 males) and test cohort of 30 (20 males) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…The Chula formula technique is more significant than the Colombian formula technique because the subject's height has a relationship with the trachea's length. This study also supports the research of Mukherjee et al 6 explained that gender and weight did not affect determining the length of TT insertion. In this study, the combination of height and weight (Colombian formula) was no better than the height formula (Chula formula).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Chula formula technique is more significant than the Colombian formula technique because the subject's height has a relationship with the trachea's length. This study also supports the research of Mukherjee et al 6 explained that gender and weight did not affect determining the length of TT insertion. In this study, the combination of height and weight (Colombian formula) was no better than the height formula (Chula formula).…”
Section: Discussionsupporting
confidence: 92%
“…Too shallow TT insertion possibly hit the vocal cords so that the inflammation can trigger sympathetic stimulation, trauma, repetitive compression of the laryngeal nerve, and an increased risk of involuntary extubation. 6,7 The traditionally length TT insertion was 21 cm in women and 23 cm in men. Several scientific publications show that more than 33.4% of TT are incorrectly placed.…”
Section: Introductionmentioning
confidence: 98%
“…To date, a few studies have investigated various parameters for determining ETT insertion and final positioning. Some of them are based on vocal cord-carina distance and tracheal length [12], stature, and incisor manubrio-sternal joint length [13]. Further, an individual's height [14] and various anatomical landmarks have also been employed to predict airway length resulting in varying outcomes [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some of them are based on vocal cord-carina distance and tracheal length [12], stature, and incisor manubrio-sternal joint length [13]. Further, an individual's height [14] and various anatomical landmarks have also been employed to predict airway length resulting in varying outcomes [13]. A seminal study reported that the tracheal midpoint corresponds internally to a line drawn between the medial heads of the clavicles and hence clavicles have also been employed as a reference point [15].…”
Section: Discussionmentioning
confidence: 99%
“…Techanivate et al found moderate correlation between height of a person and canine to carinal length [8]. Evron et al used some topographic methods for detection of airway length [9].Mukherjee et al conducted a study for bedside prediction of airway length by measuring upper incisormanubriosternal joint length[10].…”
mentioning
confidence: 99%